Examining the Influence of Peer Relationships on Academic Achievement at Al-Ikhlash Female Islamic Boarding School - Imani, Aisyah (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2025)
A peer group is an environment where people of the same age and status interact intensively and regularly. This environment can influence their academic achievement in both positive and negative ways. This also applies to 2nd-grade Tarbiyatul Mu’allimat al-Islamiyah (TMI) who often disturb their peers or talk too much during study hours, resulting in decreased concentration and unsatisfactory learning outcomes, with grades still below the passing standard. This article aims to determine how peers influence the learning outcomes of second-grade Tarbiyatul Mu’allimat al-Islamiyah (TMI) students at Al-Ikhlash Female Modern Islamic Boarding School. The research method used is quantitative, with a sample of 24 students from a total population of fewer than 30 students. Saturation sampling was used for sample selection, which is more appropriate in cases where the population is relatively small, specifically less than thirty. Data was collected through interviews using questionnaires. The research results show that peer influence is 53.7%, the coefficient of determination indicates an R Square value of 0.537, which indicates an influence of 53.7% between the peer variable (X) and the learning outcome variable (Y).